On special solutions of Zakharov-Schulman equations - Bilman, Deniz. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In this work, two types of special solutions for Zakharov–Schulman equations are studied. Existence of standing wave solutions are established by utilizing variational methods. First set conditions on the operators for the existence of Arkadiev– Pogrebkov–Polivanov type travelling wave solutions are derived. It is observed that there exist blow-up profiles whenever either of these special solutions exist.
Keywords: Hamiltonian systems.; Nonlinear waves.